An optimal parallel minimax tree algorithm - Kirkpatrick, D.G.; Przytycka, T. (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
An log n time n/log n processor CREW PRAM algorithm to construct an alphabetic minimax tree is presented. The algorithm achieves these optimal bounds by a combination of existing parallel techniques (applied in novel ways) and a new technique, called accelerated valley filling. Parallel algorithms for several other versions of the minimax tree problem are also discussed.< >